Effect of Hyperglycemia-Related Acute Metabolic Disturbance on Thyroid Function Parameters in Adults - Iwamoto, Yuichiro; Kimura, Tomohiko; Tatsumi, Fuminori; Sugisaki, Toshitomo; Kubo, Masato; Nakao, Erina; Dan, Kazunori; Wamata, Ryo; Iwamoto, Hideyuki; Takahashi, Kaio; Sanada, Junpei; Fushimi, Yoshiro; et al. (Frontiers in Endocrinology, 2022)
Aim: Non-thyroidal illness (NTI) is a condition in which the hypothalamic-pituitary-thyroid system and thyroid hormone metabolism are abnormal due to non-thyroidal diseases. Although NTI has been reported to occur in hyperglycemic emergencies in children, there have been few studies in adult cases. The aim of this study was to investigate a possible influence of hyperglycemia-related acute metabolic disturbance on thyroid function parameters in adults. Methods: We performed this study with adult diabetic patients who were hospitalized in our institution for diabetic ketosis (DK), diabetic ketoacidosis (DKA), or hyperglycemic hyperosmolar syndrome (HHS) and whose thyroid hormone levels were measured. Results: The frequency of NTI in the DKA, HHS, and DK groups was 80%, 70%, and 50%, respectively, and thyroid-stimulating hormone (TSH) and free thyroxine 3 (FT3) were significantly improved after treatment for hyperglycemia. The extent of decrease in FT3 level was associated with various parameters such as blood glucose levels, serum osmotic pressure and ketone bodies. Furthermore, multiple regression analysis showed that 3-hydroxybutyrate and albumin were independently associated with the decrease in FT3 level. Conclusion: Acute metabolic failure associated with hyperglycemia tends to be associated with a high rate of NTI and low FT3 levels at the start of treatment. The data in this study clearly shows that transient hypothyroidism is frequently observed in subjects with acute metabolic disorders such as DKA, HHS and DK. In addition, we should bear in mind that thyroid hormone replacement therapy is not necessary in subjects with hypothyroidism due to DKA, HHS and DK, especially when overt symptoms of hypothyroidism are not observed.